The Lost Social Context of Recovery Psychiatrization of a Social Process - Topor, Alain; Boe, Tore Dag; Larsen, Inger Beate (Frontiers in Sociology, 2022)
From being a concept questioning the core of psychiatric knowledge and practice, recovery has been adopted as a guiding vison for mental health policy and practice by different local, national, and international organizations. The aim of this article is to contextualize the different understandings of recovery and its psychiatrization through the emergence of an individualizing and de-contextualized definition which have gained a dominant position. It ends with an attempt to formulate a new definition of recovery which integrates people in their social context. Research results from various follow-up studies showing the possibility of recovery from severe mental distress have stressed the importance of societal, social and relational factors as well of the person’s own agency when facing their distress and reactions from their environment. These researches were published in the 1970s and 80s; a period of struggle for liberation from colonialism, of struggle by women and black people for their civil rights, and a time of de-institutionalization of services directed towards the poor, elderly, handicapped, prisoners, and people with mental health problems. Recovery research pointed at the central role of individuals in their recovery journey and it was understood as a personal process in a social context. However, with neo-liberal political agenda, the personal role of individuals and their own responsibility for their well-being was stressed, and contextual understandings and the role of social, material and cultural changes to promote recovery faded away. Thus, during recent decades recovery has been mostly defined as an individualistic journey of changing the persons and their perception of their situation, but not of changing this situation. Contextual aspects are almost absent. The most quoted definition accepts the limits posed by an illness-based model. This kind of definition might be a reason for the wide acceptance of a phenomenon that was initially experienced as a break with the bio-medical paradigm. Recently, this dominant individualized understanding of recovery has been criticized by service users, clinicians and researchers, making possible a redefinition of recovery as a social process in material and cultural contexts.